The Effect of HLB Surfactant Value on The Characteristics of Emulsion Biodiesel Palm Oil Using Homogenizer - Damayani, Intan Ardina; Paramita, Vita; Yulianto, Mohamad Endy (Journal of Vocational Studies on Applied Research, 2021)
The process of making water emulsion in palm oil biodiesel is assisted by using two types of surfactants with different HLB values, namely Tween 80 and Span 80. This study aims to determine the characteristics of palm oil biodiesel emulsion made using a homogenizer with different HLB values, surfactant composition and water content in each sample. Density, viscosity, stability and microscopy tests were carried out to determine the characteristics of palm oil biodiesel emulsion. The results were obtained in the form of the highest density and viscosity values found in samples with high HLB values, surfactant composition and water content, while for stability test results were found in samples with low HLB values, surfactant composition and low water content. This shows that the difference in the value of HLB used will affect the amount of surfactant composition and moisture content in the sample composition and will affect the density, viscosity and stability of the palm oil biodiesel emulsion formed.